Strategies for Improving Teacher Service Quality Through the Effectiveness of ICT Implementation, Servant Leadership, Knowledge Management, Interpersonal Communication, and Job Satisfaction (Using Path Analysis and Sitorem on Civil Servant Teachers at Public Junior High Schools in Bogor Regency) - Sains Rusnadi; Henny Suharyati; Sri Setyaningsih (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study aims to determine the strength of variables that are suspected to affect the quality of teacher services. These variables are the Effectiveness of ICT Application, Service Leadership, Knowledge Management, Interpersonal Communication, and Job Satisfaction both directly and indirectly with the variables of teacher service quality. The population of this study is 1,490 civil servant teachers of Bogor Regency State Junior High School. The sampling technique uses Random Sampling, with the Taro Yamane formula with a sample of 211. The results of the study show that: 1) The effectiveness of ICT Implementation (X1) has a direct effect on the Quality of Teacher Services (Y), 2) Servant Leadership (X2) has a direct effect on the Quality of Teacher Services (Y), 3) Knowledge Management (X3) has a direct effect on the Quality of Teacher Services (Y), 4) Interpersonal Communication (X4) has a direct effect on the Quality of Teacher Services (Y), 5) Job Satisfaction (X5) has a direct effect on the Quality of Teacher Services (Y), 6) The Effectiveness of ICT Application (X1) has a direct effect on Job Satisfaction (X5), 7) Serving Leadership (X2) has a direct effect on Job Satisfaction (X5), 8) Knowledge Management (X3) has a direct effect on Job Satisfaction (X5), 9) Interpersonal Communication (X4) has a direct effect on Job Satisfaction (X5), 10) Effectiveness of ICT Application (X1) has an indirect effect on the Quality of Teacher Services (Y) through Job Satisfaction (X5), 11) Serving Leadership (X2) has an indirect effect on the Quality of Teacher Service (Y) through Job Satisfaction (X5), 12) Knowledge Management (X3) has an indirect effect on the Quality of Teacher Service (Y) through Job Satisfaction (X5), 13) Interpersonal Communication (X4) has an indirect effect on the Quality of Teacher Service (Y) through Job Satisfaction (X5). The results of the SITOREM analysis show that there are 12 indicators out of 6 variables that must be improved immediately and 22 indicators out of 6 variables are maintained or developed. This study concludes that strengthening the effectiveness of ICT Application, service leadership, knowledge management, interpersonal communication, and job satisfaction can improve the quality of teacher services.